Ami armihuariensis, a new species from Peru (Araneae: Theraphosidae: Theraphosinae) - Kaderka, Radan (2014)
Ami armihuariensis sp. nov. from Cuzco region, Peru is described, diagnosed and figured. Males of Ami armihuariensis sp. nov. differ from all other congeners, except A. pijaos, by the presence of only one retrolateral process on male palpal tibia, from A. pijaos by the granulation in tegular area of male palpal bulb. Additionally,  photographs of A. yupanquii spermatheca  are for the first time presented in order to emphasize the characteristic shape of spermathecae in this genus.